Oocyst shedding by green-winged-saltator (Saltator similis) in the diagnostic of coccidiosis and Isospora similisi n. sp. (Apicomplexa: Eimeriidae) - Coelho,Cleide Domingues (2013)
Diurnal periodicity is a phenomenon that has been observed in coccidian of Isospora parasites of passerines, which have been eliminated great number of oocysts at dusk. The objective of this study was to evaluate the occurrence of periodicity of oocysts presence in the green-winged-saltator Saltator similis, and its use in the diagnosis of coccidiosis in wild birds in captivity. A total of 220 fecal samples were collected from birds, apprehended from illegal trading and kept in quarantine in CETAS∕IBAMA, in the morning and late afternoon, from May to November 2010. It was observed that 1.82% of the samples collected in the morning were positive, while 31.36% of samples were positive in the late afternoon. In addition, the number of oocysts shed was greater in the afternoon. Therefore, it was concluded that the sampling in the late afternoon provided greater reliability for the diagnosis of coccidiosis in green-winged-saltators. Moreover, in this study a new isosporoid coccidian parasite from the green-winged-saltator S. similis was observed and is herein described. Isospora similisi n. sp. oocysts are spheroidal to sub-spheroidal, 27.5 × 25.9 µm, with a smooth and bi-layered wall, ∼1.2 mm. Micropyle and oocyst residuum are absent, but splinter-like or comma-like granules are present. Sporocysts are ellipsoidal or slightly ovoidal, 17.4 × 12.2 mm. A stieda body and substieda body are present. The sporocyst residuum is composed of granules of different sizes. Sporozoites are vermiform with a single refractile body and a nucleus. This is the fourth description of an isosporoid coccidium infecting S. similis and the sixth description from Cardinalidae.